Assistance in Measuring Patient Satisfaction with Antenatal Care Services at the Cimalaka Community Health Center, Sumedang Regency - Evi Kusumahati; Nike Arta Puspitasari; Rumiyati (Jurnal Sentra Pengabdian, 2026)
Quality antenatal care (ANC) services are crucial for safeguarding the health of pregnant women and their fetuses. However, community participation in providing feedback on the quality of services received still needs to be enhanced as part of efforts to improve healthcare quality. This initiative aimed to increase pregnant women's understanding of ANC service standards, assist the community in evaluating the services received, and identify aspects of service at the Cimalaka Community Health Center (Puskesmas)—located in Sumedang Regency—that require maintenance or improvement. The study employed a Participatory Action Research (PAR) method, incorporating educational activities, guidance on completing satisfaction evaluation instruments, interactive discussions, and collaborative reflection among participants, healthcare workers, and the community service team. The program engaged 137 multigravida pregnant women. The results demonstrated that participants gained a better understanding of ANC quality indicators, the importance of adhering to standard ANC visit schedules, and patients' rights to quality healthcare. The service evaluation process provided an opportunity for participants to share their experiences, expectations, and feedback regarding the care they received. The majority of participants rated the ANC services at the Cimalaka Community Health Center positively, particularly regarding staff attentiveness, ease of consultation, and the availability of service facilities. This community service initiative benefited the public by increasing knowledge and engagement in healthcare service evaluation, while also providing valuable input to the health center for the continuous improvement of antenatal care quality